Diamondiferous deposits in the Jequitaí area (Minas Gerais, Brazil): A consequence of neotectonic processes - Penha, Ulisses Cyrino; Karfunkel, Joachim; Angeli, Nelson [UNESP] (Schweizerbart, 2005)
Diamonds obtained from small scale mining near Jequitaí and surrounding villages are extracted from Tertiary conglomerates and Quaternary gravels of the Rio Jequitaí. Eocretaceous conglomerates, which are locally poorly diamondiferous, cover parts of the Serra da Água Fria and Serra do Cabral. They are of no economic importance. Analyses of neotectonic, post-Miocene features support a transpressive regime that gave rise to N-S to N25°E transcurrent faults, and WNW normal faults. The main evidence for neotectonic processes are inclined Tertiary sediments, drainage captures, striated laterites of Miocene age, and tilting of blocks that form the Rio Jequitaí graben. Diamonds in the Tertiary terraces derived from the Eocretaceous conglomerates, which were affected by neotectonic processes, followed by erosion and concentration during redeposition of sediments. © 2005 E. Schweizerbart'sche Verlagsbuchhandlung.